65‐3: The Quantization of Cybersickness Level Using EEG and ECG for Virtual Reality Head‐Mounted Display - Lin, Yi-Tien; Chien, Yu-Yi; Wang, Hsiao-Han; Lin, Fang-Cheng; Huang, Yi-Pai (SID International Symposium Digest of technical papers, 2018)
Cybersickness is a critical problem of virtual reality (VR) applications. This study found an objective method to quantize the cybersickness level using the bio‐signals, including electroencephalography (EEG) and electrocardiography (ECG). These results demonstrated a higher level of cybersickness caused power of gamma band (>32Hz) stronger and enhanced subjects' heart rate as well. The variations of these bio‐signals could be an indicator to quantize people's cybersickness level and be applied for a warning system for VR devices.